The Concept of the FSES HE of the Fourth Generation for Engineering Education in the Context of Implementing the Assignments of the President of Russia - A. I. Rudskoy; A. I. Borovkov; Р. I. Romanov (Высшее образование в России, 2021)
Within the framework of the activities of the Coordinating Council of the Ministry of Science and Higher Education of the Russian Federation in the field of education “Engineering, Technology and Technical Sciences”, proposals have been developed for the implementation of a set of tasks for the development of higher education set by the President of Russia. The necessity of implementing different methodological and normative approaches to different areas of higher education is argued. The authors substantiate the concept of the fourth generation Federal State Educational Standard for the engineering field of education. A new approach to the organization of admission to universities is proposed, which allows students to choose the direction of training after completing the second year of study. An innovative structure of lists of specialties and areas of preparation of higher education is presented, which provides the possibility of implementing the concept of the fourth generation Federal State Educational Standard, as well as greater flexibility and enlargement of the lists.